PENGEMBANGAN MEDIA PEMBELAJARAN PETA SEJARAH BERBANTUAN ArcGIS PADA MATERI KERAJAAN ISLAM DI SUMATERA - Nurfadhlila; Zulfa; Liza Husnita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to develop historical map learning media for the History subject, specifically the topic "Islamic Kingdoms." This study used a Research and Development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. However, this research only went to three stages: Analysis, Design, and Development. The research subjects were teachers and 10th-grade students at SMA Negeri 1 Hulu Kuantan. In the definition stage, a needs and materials analysis was conducted to design a documentary film that aligned with the analysis. The design stage involved selecting materials and media appropriate to the analysis. The development stage involved creating a historical map using ArcGIS, which was then validated by material and media experts. The validation results showed that the developed historical map fell into the very valid media validation category (100%), and the valid material and language validation category (57.14%). Next, the historical map was piloted on 24 10th-grade students. The trial results showed that historical maps were "very practical" for use in learning, with an average practicality score of 88.8% from teachers and 84.03% from students. Based on the research findings, ArcGIS-assisted Historical Map Learning Media for the Islamic Kingdoms in Sumatra topic using the ADDIE development model can be developed.